Effect of substrate preheating on the texture, phase and nanohardness of a Ti–45Al–2Cr–5Nb alloy processed by selective laser melting. (June 2016) - Li, Wei; Liu, Jie; Zhou, Yan; Wen, Shifeng; Wei, Qingsong; Yan, Chunze; Shi, Yusheng
Abstract: The crystallographic texture, phase composition and evolution, and nanohardness of a Ti–45Al–2Cr–5Nb alloy processed by selective laser melting (SLM) at various substrate preheating temperatures were investigated. The α2 phase decreases whereas the γ and B2 phases increase with increasing preheating temperature, and the relationship in orientation between B2, α2 and γ phases is described as follows: 11 2 ̅ 0 α 2 / / 111 γ / / 111 B 2 . The SLM-processed TiAl alloy shows much higher nanohardness than its traditional casting counterpart, which increases with the increase of preheating temperature. The findings would be a valuable reference for fabricating TiAl components with acceptable texture, phase compositions and nanohardness by SLM. Graphical abstract: